2007
DOI: 10.1029/2006gl028634
|View full text |Cite
|
Sign up to set email alerts
|

Annual modulation of seismicity along the San Andreas Fault near Parkfield, CA

Abstract: We analyze seismic data from the San Andreas Fault (SAF) near Parkfield, California, to test for annual modulation in seismicity rates. We use statistical analyses to show that seismicity is modulated with an annual period in the creeping section of the fault and a semiannual period in the locked section of the fault. Although the exact mechanism for seasonal triggering is undetermined, it appears that stresses associated with the hydrologic cycle are sufficient to fracture critically stressed rocks either thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
70
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 34 publications
7
70
2
Order By: Relevance
“…Those extensive results combine to provide an evolution from a working hypothesis to an established tool in the search for an understanding of earthquake generation phenomena. Christiansen et al (2007) concluded that the evidence for seasonal variations in seismicity at Parkfield, California, is supported by all statistical tests, and the timing of seismicity seems to be linked to the hydrologic cycle. This conclusion supports results published 23 years earlier by McClellan (1984), who noted that the observed frequency of earthquakes occurring in the spring over a 25-year interval before the San Francisco earthquake of 1906 significantly exceeded seasonal frequencies expected from random variations in the earthquake rate.…”
Section: Current Status Of the Hydroseismicity Hypothesismentioning
confidence: 94%
“…Those extensive results combine to provide an evolution from a working hypothesis to an established tool in the search for an understanding of earthquake generation phenomena. Christiansen et al (2007) concluded that the evidence for seasonal variations in seismicity at Parkfield, California, is supported by all statistical tests, and the timing of seismicity seems to be linked to the hydrologic cycle. This conclusion supports results published 23 years earlier by McClellan (1984), who noted that the observed frequency of earthquakes occurring in the spring over a 25-year interval before the San Francisco earthquake of 1906 significantly exceeded seasonal frequencies expected from random variations in the earthquake rate.…”
Section: Current Status Of the Hydroseismicity Hypothesismentioning
confidence: 94%
“…These effects are shown to reduce lithostatic load (minimal stress axe: σ 3 ) and to allow rupture of faults and facilitate rock mass failure. Increased pore groundwater pressure during glacial melting, permafrost degradation or heavy rainfall events have also been evoked to induce enhanced seismicity (Costain et al, 1987;Davies et al, 2001;Saar and Manga, 2003;Christiansen et al, 2007) and landsliding (Caine, 1982;Gruber and Haeberli, 2007). The rock slope in the studied Tinée valley is heavily fractured, structurally and lithologically contrasted (shistosity, shear zone).…”
Section: Impact Of Climate Change On Slope Morphologymentioning
confidence: 97%
“…The hydrologically induced pore pressure variations are primarily limited to the shallow depths of 0-5 km (Hainzl et al, 2006). The 2012 M w 5.4 Ernabella earthquake (event 2 in Figure 4) possibly occurred in a low permeability and porosity fault zone that would cause a time lag with respect to the local groundwater maximum, indicating that the process of fault weakening in the lowpermeability fault zone could be delayed (Christiansen et al, 2007). The deeper portions of the ancient faults may be effectively healed, and may not anymore represent preexisting faults that could easily slip.…”
Section: Causes Of Shallow Earthquakes In the Petermann Rangesmentioning
confidence: 99%